Réponses

2013-04-04T11:05:35+02:00

1. x² - 10x + 12 = x² - 10x + 25 - 13 = (x² - 10x + 25) - 13 =(x-5)² - 13

2.Aire du rectangle : 6.4 = 24 cm²

 aire croix 6x + 4x - x² = -x² + 10x

 aire restante = 24 -( -x² + 10x) = x² - 10x + 24

il faut que x² - 10x + 24 = -x² + 10x => 2x² - 20x + 24 = 0 => x² - 10x + 12 = 0

on a vu que x² - 10x + 12 = (x-5)² - 13 = 0 => x-5 = V13 =>x = 5 + V13

                                                                   => x-5 = -V13 => x = 5 - V13

mais il faut que 0 < x < 4 donc la seule solution est x = 5 - V13